Professional English Language Skills for Employability in Portugal - Ana Cunha; Anabela Mateus; Amanda Bruscato; Inês Renda (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2023)
This paper reports on the research carried out by a Portuguese university in the scope of PESE – Professional English Language Skills for Employability Across EU project, which highlights the importance of appropriate English skills for the workplace. The present study focuses on the Portuguese labor market and identifies the English skills employers currently require from their employees based on the review of a job search website and the application of questionnaires to 22 Portuguese companies, as well as 6 experienced English trainers. The data collection is part of the project’s Handbook on the current Professional English requirements throughout partner countries, from which a framework for a curriculum can be established. The curriculum will then form the basis of an e-course on professional English skills targeted toward unemployed citizens in Europe.